2016
DOI: 10.1139/cjas-2015-0177
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pregnancy and plane of nutrition during pregnancy on pancreatic digestive enzymes and insulin-containing cell cluster morphology in beef cows

Abstract: To determine effects of pregnancy (experiment 1) and plane of nutrition during pregnancy (experiment 2) on pancreatic digestive enzymes and morphology of insulin-containing cell clusters, beef cows were slaughtered, and the pancreas collected 4 wk before parturition (if pregnant or similar time on feed for nonpregnant cows). In experiment 1, mature, nonlactating cows [717 ± 70 kg; nine pregnant (PREG) and nine nonpregnant (OPEN)] were used. In experiment 2, nonlactating, pregnant cows (639 ± 68 kg) were fed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Regarding the fetal pancreatic exocrine function, some results show that nutrient restriction of ewes during mid-to-late gestation had no effect on fetal pancreatic digestive enzymes (Keomanivong et al, 2016); however, more results demonstrated that pancreatic exocrine function is affected by both nutrition and pregnancy (Awda et al, 2017;Keomanivong et al, 2017). In the present study, increased serum amylase and serum lipase in RG2 were observed in IUGR fetal pancreas, which indicated that exocrine function in fetal pancreas was affected by maternal nutritional restriction during late pregnancy.…”
Section: Discussioncontrasting
confidence: 40%
“…Regarding the fetal pancreatic exocrine function, some results show that nutrient restriction of ewes during mid-to-late gestation had no effect on fetal pancreatic digestive enzymes (Keomanivong et al, 2016); however, more results demonstrated that pancreatic exocrine function is affected by both nutrition and pregnancy (Awda et al, 2017;Keomanivong et al, 2017). In the present study, increased serum amylase and serum lipase in RG2 were observed in IUGR fetal pancreas, which indicated that exocrine function in fetal pancreas was affected by maternal nutritional restriction during late pregnancy.…”
Section: Discussioncontrasting
confidence: 40%
“…More recent studies have evaluated the effects of dietary intake restriction on pancreatic α-amylase activity in ruminants. Dietary intake restriction decreased pancreatic α-amylase activity in nonpregnant ewes [93], pregnant ewes [94,95], and pregnant beef cows [96,97]. Changes in pancreatic α-amylase activity in response to changes in dry matter or energy intake may be related to the abundance and activity of pancreatic proteins involved in energy metabolism.…”
Section: Influence Of Dry Matter and Energy Intake On Pancreatic α-Am...mentioning
confidence: 98%